Exploring EFL Pre-Service Teachers Perception of Interaction: A Case of Indonesian Creative Problem-Solving Implementation - Fatimah, Siti Khusnul; Sumardi, Sumardi; Drajati, Nur Arifah (Journal of Languages and Language Teaching, 2024)
Student-student interaction is often overlooked, yet it plays a crucial role in the learning process. Teachers’ guidance in facilitating these interactions can significantly influence students' attitudes toward the subject and their perceptions. This study investigates pre-service teachers’ perceptions of student interactions within a creative problem-solving (CPS) framework using the Initiation-Response-Feedback (IRF) model. Qualitative data were collected through in-depth interviews, artifacts, and voice recordngs, The study involved 46 pre-service teachers, 6 males and 40 females, they are undergraduate students enrolled in the Curriculum and Material Development course. The results indicate that the CPS and IRF models effectively enhanced interaction, collaboration, and critical thinking among pre-service teachers. The dynamic classroom environment fostered by these models encouraged students to engage actively with their peers, respond positively to challenges, and generate innovative ideas. Peer feedback was particularly valuable, allowing for the maturation of concepts and deeper exploration of project content and learning media. Overall, the integration of the IRF model with CPS not only improved student interaction but also facilitated a collaborative atmosphere conducive to intellectual growth in an English as a Foreign Language (EFL) classroom. This study highlights the importance of structured student interactions and provides insights into effective teaching strategies that can enrich the learning experience.